2017
DOI: 10.5812/ijpbs.9363
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Vascular Endothelial Markers and Right Ventricular Function in the Children with Asthma

Abstract: Objectives: The aim of the study was to evaluate the possible relationship of clinical severity during asthmatic exacerbation with the ventricular functions and the levels of vascular endothelial-related biomarkers endothelin-1 (ET-1) and platelet-derived growth factor-BB (PDGF-BB) in the condensed breathing air in the children with asthma. Methods: The study included a total of 80 children with acute asthmatic episode; of these, 28 had a mild, 26 had a moderate, and 26 had a severe attack. Samples of condense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
2
2
Order By: Relevance
“…In the present study, preservation of RV systolic function was confirmed by the use of the 2D STE derived RV strain which did not differ significantly between patients and controls. Preservation of RV systolic function was among the parameters reported by previous studies in asthmatic patients . In contrast to our study, Shedeed reported RV systolic dysfunction in asthmatic patients .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, preservation of RV systolic function was confirmed by the use of the 2D STE derived RV strain which did not differ significantly between patients and controls. Preservation of RV systolic function was among the parameters reported by previous studies in asthmatic patients . In contrast to our study, Shedeed reported RV systolic dysfunction in asthmatic patients .…”
Section: Discussioncontrasting
confidence: 99%
“…Preservation of RV systolic function was among the parameters reported by previous studies in asthmatic patients. [23][24][25][26] In contrast to our study, Shedeed reported RV systolic dysfunction in asthmatic patients. 28 The discrepancy in the results regarding RV function may be again attributed to differences in the severity and duration of asthma among the studied populations.…”
Section: Right Heart Parameterscontrasting
confidence: 99%
See 1 more Smart Citation
“…While we can explain diastolic dysfunction in moderate asthma group by pulmonary hypertension, diastolic dysfunction in mild asthma group may be due to cardiac stress during asthma exacerbations resulting from acute increase in pulmonary artery pressure and the concomitant inflammatory response. Released cytokines in such situation was reported as a direct cause of myocardial impairment [27,28] .…”
Section: Discussionmentioning
confidence: 99%